Graph-theoretic concepts in computer science : 42nd International Workshop, WG 2016, Istanbul, Turkey, June 22-24, 2016, Revised selected papers /: 42nd International Workshop, WG 2016, Istanbul, Turkey, June 22-24, 2016, Revised selected papers. (2016) - Unknown
No abstract available